Hepatic copper and other trace mineral concentrations in dogs with hepatocellular carcinoma - Cailin C. Harro; Rebecca C. Smedley; John P. Buchweitz; Daniel K. Langlois (Journal of Veterinary Internal Medicine, 2019)
Abstract Background Hepatocellular carcinoma (HCC) is the most common primary liver tumor in dogs. Abnormalities in hepatic copper, iron, zinc, and selenium concentrations increase risk for HCC development in other species, but trace mineral concentrations have not been evaluated in dogs with HCC. Objectives To investigate hepatic trace mineral concentrations in dogs with HCC. Animals Archived liver specimens from 85 dogs with HCC and 85 control dogs. Methods Retrospective case‐control study. A histopathology database was searched to identify dogs with HCC (test population) and an age‐matched control population. Demographic information was retrieved, and H&E and rhodanine stained slides were reviewed for all cases. Copper, iron, zinc, and selenium concentrations were determined in noncancerous liver tissues (test and control population) and in HCC tissues (test population) using inductively coupled plasma mass spectrometry. Results Hepatic copper concentrations (non‐neoplastic hepatic tissue) were greater in test population dogs (median, IQR; 294.9 μg/g, 233.5‐475.9 μg/g) than in control dogs (202.8 μg/g, 135.0‐295.3 μg/g; P < .001). Hepatic zinc concentrations in test (132.1 μg/g,108.6‐163.2 μg/g) and control dogs (151.5 μg/g, 117.1‐184.5 μg/g) also were different (P = .03). Within test population dogs, all trace mineral concentrations were decreased in the HCC tissue as compared to the non‐neoplastic hepatic tissue (all P < .001). Conclusions and Clinical Importance Hepatic copper accumulation and other abnormalities in hepatic trace mineral concentrations could be involved in the pathogenesis of HCC in some dogs.